Influence Of Mineral Substances On Potato Growth And Development In Moderate Salinity (On The Example Of Syrdarya Region) (Eurasian Scientific Herald, 2023)
The influence of mineral elements on the growth and development of potatoes, yield, quality of the crop and efficiency indicators of the combination of various minerals to Piskom and Sante potato varieties were determined. For this purpose, researches were carried out in experimental fields and farms located in the "Experimental Biology" laboratory of Gulistan State University, the Navbahor farm of the university in Sirdarya region, and Khojamushkent massif of Yangiabad district of Jizzakh region. The optimal nutrient medium was determined under the influence of different proportions of NPKZnMg. When potato plants were exposed to N90P60K40Zn5Mg3kg/ha nutrient options, photosynthesis productivity, chlorophyll content, and mineral content in tubers were high. In all other concentrated nutrient variants, compared to this variant, the reduction of photosynthesis productivity and number of leaves, leaf surface area was observed. It was found that the nutrient option with the concentration of N90P60K40Zn5Mg3 kg/ha had a positive effect on the productivity of photosynthesis, the number of leaves, and the surface area of the leaf.